Parallel Curriculum : a Design to Develop Learner Potential and Challenge Advanced Learners. - Tomlinson, Carol Ann (Corwin, 2008)
Engage students with a rich curriculum that strengthens their capacity as learners and thinkers! Every learner is somewhere on a path toward expertise in a content area. This resource promotes a model for developing high-quality curriculum that moves learners along the continuum toward expertise and provides sample units and rubrics to help implement differentiated curriculum. Teachers can use four curriculum parallels that incorporate Ascending Intellectual Demand to: Determine current student performance levels Appropriately challenge all students in each subject area Extend.